1987
DOI: 10.1021/ic00253a030
|View full text |Cite
|
Sign up to set email alerts
|

Transsilylation reactions of phosphazene precursors

Abstract: The transsilylation reactions of the phosphazene precursor Me3SiN=P(OCH2CF3)Me2 (1) with a variety of chlorosilanes, dichlorosilanes, and dichlorosiloxanes were studied. Thus, treatment of 1 with chlorosilanes RMe2SiCl at 0 °C in CH2C12 solution affords the transsilylation products RMe2SiN=P(OCH2CF3)Me2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…N -Silylphosphoranimines of general formula Me 3 SiNP(X)R‘R‘ ‘ have provided access to a variety of new main group element systems, especially phosphazene polymers. Studies in our laboratories have shown that these Si−N−P compounds exhibit at least four modes of reactivity: (1) condensation to polymeric 7 (X = OCH 2 CF 3 or OPh) or cyclic and/or oligomeric (X = halogen) phosphazenes via elimination of Me 3 SiX, (2) substitution at phosphorus, (3) deprotonation−substitution at P -alkyl groups, and (4) Si−N bond cleavage reactions . The utility of N -silylphosphoranimines is enhanced by their straightforward and versatile synthesis .…”
Section: Resultsmentioning
confidence: 99%
“…N -Silylphosphoranimines of general formula Me 3 SiNP(X)R‘R‘ ‘ have provided access to a variety of new main group element systems, especially phosphazene polymers. Studies in our laboratories have shown that these Si−N−P compounds exhibit at least four modes of reactivity: (1) condensation to polymeric 7 (X = OCH 2 CF 3 or OPh) or cyclic and/or oligomeric (X = halogen) phosphazenes via elimination of Me 3 SiX, (2) substitution at phosphorus, (3) deprotonation−substitution at P -alkyl groups, and (4) Si−N bond cleavage reactions . The utility of N -silylphosphoranimines is enhanced by their straightforward and versatile synthesis .…”
Section: Resultsmentioning
confidence: 99%
“…Some related N -phosphorylphosphoranimines have been reported and structurally characterized, , but generally, they do not contain the requisite functional groups on phosphorus. The reactivity of the SiN bond in N -silylphosphoranimines toward nonmetal halides has been utilized to prepare many other SiNP and BNP 8 derivatives. It seemed appropriate, therefore, to investigate the possible synthesis of PNP systems in a similar manner.…”
Section: Introductionmentioning
confidence: 99%